Bi‐objective Model for Optimal Number and Size of Circular Facilities. Issue 2 (20th June 2016) - Miyagawa, Masashi
Abstract : This article presents a bi‐objective model for determining the number and size of finite size facilities. The objectives are to minimize both the average closest distance to facilities and the probability that a random line intersects facilities. The former represents the accessibility of customers, whereas the latter represents the interference to travelers. The average closest distance and the probability of intersecting facilities are derived for circular facilities randomly distributed in a circular city. The analytical expressions for the average closest distance and the probability of intersecting facilities demonstrate how the number and size of facilities affect the accessibility of customers and the interference to travelers. The model focuses on the tradeoff between the accessibility and interference, and the tradeoff curve provides planners with alternatives for the number and size of facilities.